The Adventures of Dr. Duncan McNab McEachran in Western Canada - Vokaty, Sandra (1979)
Duncan McNab McEachran's early history and involvement in the formation of the Montreal Veterinary College as well as in livestock inspection were reviewed. His contribution to the beginning of the ranching industry in western Canada was explored in detail. In 1881, McEachran helped to establish the Cochrane Ranche, which was the first great ranch to be started in southern Alberta. He was employed as the ranch's resident general manager until 1883, in which year the Waldrond Ranch was established. McEachran was this ranch's president and general manager until approximately 1909. During this time, he came under considerable criticism from both The MacLeod Gazette and The Calgary Herald. As Dr. McEachran maintained his obligations to the ranches while he was directing the veterinary college in Montreal as well as chief inspector of livestock for Canada, it was concluded that this feat alone would rank him as a remarkable historical figure.